Frederick Schwatka and the search for the Franklin expedition records, 1878–1880 - Savitt, Ronald (Polar Record, 2008)
ABSTRACT Frederick Gustavus Schwatka was one of America's most important Arctic explorers. While honoured in his time, he is only a footnote in the search for Sir John Franklin. He commanded, in 1878–1880, an expedition of the American Geographical Society of New York which had the aim of retrieving records from King William Island. Although none were found, he did discover a number of expedition relics and remains. His extensive sledge journey during this expedition was one of the longest recorded by a European-North American expedition, over 5232 km (3,251 statute miles). Moreover it was conducted under some of the coldest conditions ever endured in polar exploration. Schwatka's party included three Europeans, William H. Gilder, a journalist from The New York Herald , Henry Klutschak, a naturalist, and Frank E. Melms, an experienced seaman, and ‘Eskimo Joe’ Ebierbing, an Inuit who had served on previous expeditions in search of Franklin. ‘Schwatka's search’, as it was known, concluded efforts to discover the fate of the Franklin expedition in the nineteenth century. It laid the groundwork for the important expeditions in the twentieth century that revealed new information concerning the fate of Franklin's men. Schwatka's expedition was without death or deprivation. Much of his success was based on a clearly defined plan and on adopting Inuit practices including living off the land, lessons he learned from his experiences with American Indians as part of his military assignments. Born in Illinois, he was educated at West Point, the United States Military Academy, acquitted himself well in the Indian Wars and then went on to qualify for the bar and secured a medical degree during his military service. He died an early and unfortunate death at the age of 43. The research reported in this article provides an understanding of the factors that shaped Schwatka and the skills that he used in this expedition.